2001
DOI: 10.1038/sj.mp.4000885
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of nicotinic acetylcholine receptors by inhibitors of monoamine uptake

Abstract: A study was made of the effects of several monoamine-uptake inhibitors on membrane currents elicited by acetylcholine (ACh-currents) generated by rat neuronal ␣2␤4 and mouse muscle nicotinic acetylcholine receptors (AChRs) expressed in Xenopus laevis oocytes. For the two types of receptors the monoamine-uptake inhibitors reduced the ACh-currents albeit to different degrees. The order of inhibitory potency was norfluoxetine Ͼ clomipramine Ͼ indatraline Ͼ fluoxetine Ͼ imipramine Ͼ zimelidine Ͼ 6-nitro-quipazine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 38 publications
4
29
0
Order By: Relevance
“…In this line is the reported association between depression and smoking, likely due to desensitization by nicotine of nAChRs (Mineur & Picciotto, 2010;Philip et al, 2010;Shytle et al, 2002). Also, consistent with this cholinergic hypothesis is the observation that a number of key antidepressants such as the selective serotonin reuptake inhibitors (SRIs) fluoxetine, sertraline, paroxetine and citalopram, the selective noradrenaline reuptake inhibitor (NRI) reboxetine, the noradrenaline-dopamine reuptake inhibitor bupropion, and tricyclics amitriptyline, imipramine, and nortriptyline have all been shown to possess antagonistic activities at nAChRs Arias et al, 2010a;Arias et al, 2010b;Bianchi, 2008;Fryer & Lukas, 1999a;Hennings et al, 1997;López-Valdés & García-Colunga, 2001;Shytle et al, 2002). On the other hand, nicotine itself and some nicotinic agonists or antagonists, can potentiate the antidepressant-like effects of SRIs and NRIs in rodent models of depression (Andreasen et al, 2011;Popik et al, 2003).…”
Section: Jpet#250969 Introductionsupporting
confidence: 51%
“…In this line is the reported association between depression and smoking, likely due to desensitization by nicotine of nAChRs (Mineur & Picciotto, 2010;Philip et al, 2010;Shytle et al, 2002). Also, consistent with this cholinergic hypothesis is the observation that a number of key antidepressants such as the selective serotonin reuptake inhibitors (SRIs) fluoxetine, sertraline, paroxetine and citalopram, the selective noradrenaline reuptake inhibitor (NRI) reboxetine, the noradrenaline-dopamine reuptake inhibitor bupropion, and tricyclics amitriptyline, imipramine, and nortriptyline have all been shown to possess antagonistic activities at nAChRs Arias et al, 2010a;Arias et al, 2010b;Bianchi, 2008;Fryer & Lukas, 1999a;Hennings et al, 1997;López-Valdés & García-Colunga, 2001;Shytle et al, 2002). On the other hand, nicotine itself and some nicotinic agonists or antagonists, can potentiate the antidepressant-like effects of SRIs and NRIs in rodent models of depression (Andreasen et al, 2011;Popik et al, 2003).…”
Section: Jpet#250969 Introductionsupporting
confidence: 51%
“…All the I-V relations showed that the equilibrium potential remained unaltered (ca. 12 mV), and all displayed the inward rectification characteristic of ACh current mediated by neuronal nAChRs, 10,18 such that at voltages more positive than zero the membrane current was near zero.…”
Section: Voltage Effects Of Zinc and Fluoxetine On Neuronal Nachrsmentioning
confidence: 99%
“…For instance, they are modulated by cations, [5][6][7][8] 5-HT, 9-13 various agonists and antagonists of different types of 5-HT receptors, [9][10][11][12]14 as well as inhibitors of monoamine transporters that are used as antidepressants. 9,12,[15][16][17][18][19][20] The most common action of clinically used antidepressants on nAChRs appears to be a noncompetitive inhibitory process, 9,12,[15][16][17][18][19][20] and it is probable that this action contributes to improving depressed mood states. 21 On the other hand, zinc is contained in neurons that are widely distributed throughout the nervous system; 22 and it is released from GABAergic and glutamatergic nerve endings, 23,24 reaching an extracellular concentration of B300 mM.…”
Section: Introductionmentioning
confidence: 99%
“…Close functional interactions between nAChRs and monoamine neurons, the targets of clinically used antidepressants, have been demonstrated by experiments modifying nAChRs by inhibiting monoamine reuptake (Lopez-Valdes and Garcia-Colunga, 2001). Therefore, it is possible that clinically-used antidepressants such as brain monoamine reuptake inhibitors are effective against these NC-induced depressive behavioral alterations.…”
Section: Introductionmentioning
confidence: 99%